The Effectiveness of Emotional Freedom Technique (EFT) Therapy in Reducing Dysmenorrhea Pain Scale in Adolescents in Gampong Peunalom 2 Tangse, Pidie Regency - Mufida, Nurlela; Mua’lim, Azhar; Ismuntania; Nazari, Nuri (International Journal on ObGyn and Health Sciences, 2024)
Dysmenorrhea has an impact on disruption of daily activities in adolescents caused by menstrual pain. One way to reduce pain can be done by applying emotional freedom technique (EFT), which can be said to be the psychological version of acupressure therapy. EFT does not use needles, but rather aligns the body's energy system at the body's meridian points, namely by tapping with the fingertips. Research Objective: to determine the effectiveness of EFT therapy in reducing the pain scale of dysmenorrhoea in adolescents in Gampong Peunalom 2 Tangse, Pidie Regency. Research methodology: this research is quasi-experimental with a "pretest – posttest control group" research design using the T-test technique. Population and Sample: The population in this study were young women in Gampong Peunalom 2 Tangse, Pidie Regency, namely 98 young women, while the sample was 10 people, with the sampling technique being purposive random sampling. This research was divided into two groups, namely the control group which was not given treatment and the experimental group which was given EFT therapy treatment. Research Results: The majority of dysmenorrhea pain levels before being given EFT therapy to teenagers in Gampong Peunalom 2 Tangse, Pidie Regency were in category 6 (moderate pain), the majority of dysmenorrhea pain levels after being given EFT therapy to teenagers in Gampong Peunalom 2 Tangse, Pidie Regency were in category 3 (mild), Conclusion: There are differences between the groups who received the intervention and those who did not. Suggestion: It is recommended that respondents add information about EFT therapy because this therapy is useful for reducing pain felt during menstruation